Emotional and Behavioral Problems Among Senior High School Adolescents - Keswari Aji Patriawati; Wiradi Suryanegara; Tiara Angelica Lucita Abineno (International Journal Of Health Science, 2026)
Emotional and behavioral problems among adolescents represent a critical issue influencing psychological and social development during a transitional phase of life. The aim of this study is to describe the prevalence and patterns of emotional and behavioral difficulties among adolescents at SMA Kristen Citra Bangsa Kupang, East Nusa Tenggara in 2024. This cross sectional study was conducted from July to August 2024 with a sample of 391 students from grades X to XII. Data collection was performed using the standardized Strengths and Difficulties Questionnaire (SDQ) to measure dimensions including emotional symptoms, conduct problems, hyperactivity, peer relationship issues, and prosocial behavior. The findings indicate that abnormal emotional symptoms were significantly more prevalent in female students (22.5%) than in males (4.9%), while abnormal prosocial behavior was more frequently observed in males (2.3%). Age-based analysis revealed that abnormal emotional problems peaked at age 15 (19.6%), whereas hyperactivity reached its highest abnormal levels at age 16 (4.8%). The study concludes that adolescent emotional and behavioral issues manifest in distinct patterns influenced by age and gender. These results synthesize the need for systematic mental health screening within schools to facilitate early intervention. Implementing gender-specific support and age-appropriate psychological services is essential to mitigate long-term negative consequences, such as academic decline and social withdrawal, thereby ensuring optimal adolescent development in the region.